A mother and son with Noonan syndrome resulting from a PTPN11 mutation: first report of molecularly proven cases from Turkey - Demir, Korcan; Yntema, Helger G; Altincik, Ayça; Böber, Ece (The Turkish Journal of Pediatrics, 2010)
Noonan syndrome is an autosomal dominant disorder characterized by short stature, typical craniofacial features, and congenital heart defects. The underlying genetic defects were not clear until 2001. This report is the first to describe a molecular analysis and associated clinical features of a Turkish mother and son, who were clinically diagnosed as Noonan syndrome when the boy was referred to our department due to short stature. The analysis revealed an A –> G transition at position 923 in exon 8 of the PTPN11 gene, indicating an Asn308Ser substitution.